Ideology Behind the Covers of the Bestselling Books in Iran: Female Narrators in War Literature. - Ghandeharion, Azra; Tekiyeh, Maryam Sadat Mousavi (Frontiers: A Journal of Women Studies, 2019)
The article looks into the business of book covers with the significance of and rationale behind well-designed, textual, and pictorial paratextuals on the book covers of the bestselling war memoirs, specifically memoirs with a female narrator published in Iran. It demonstrate the politics of book covers, discussing how gender expectations impacted author representations, requiring both tears and smiles by female authors while always emphasizing the war heroine's role as wife and mother.